Modernity and the writing the sassanid history: sassanid irrigation system as part of power- irrigation relations in the light of whitfogel theory. - Maghdid, Botan; Alee, Omar (Humanities Journal of University of Zakho, 2023)
The aim of this research stems from the proceedings of the "Ancient Iranian Water Systems Seminar" which took place at Durham University in 2011. During the conference various papers were argued that while the small-scale water systems of Ancient Iran from 8000 to 1000 B.C.E were likely a product of human ingenuity and adaptation. Simultaneously, many agreed that although there was a significant increase in the construction of water management systems on a large scale after this period, some of which were likely built by imperial authorities, it cannot be assumed that all of them were the result of imperial management. Therefore, the power- irrigation management during the Sasanian period needs more investigations. This article, then, exam the power- irrigation management relations of the Sasanian era. It critically challenges the Karl Wittfogel’s hydraulic societies theory, which is widely recognized as one of the most significant theories in the fields of power relations and irrigation management. According to Wittfogel, hydraulic societies emerge in arid or semi-arid areas where large-scale irrigation systems are essential for agriculture, and require an authoritative power capable of developing such systems. Consequently, power is concentrated in the hands of rulers and bureaucrats who control the distribution of water and resources. However, this study argues that the Sasanian dynasty’s focus on irrigation projects was not driven by a desire for control, but rather seen as a responsibility of power.